2018
DOI: 10.1016/j.surfcoat.2018.01.068
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous nitriding behaviour of 33CrMoV12-9 steel: Evolution of the grain boundaries precipitation and influence on residual stress development

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible.This is an author-deposited version published in: https://sam.ensam.eu Handle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Traditional gas nitriding (TGN), a typical thermochemical surface treatment, has been particularly effective in improving the hardness, wear resistance and fatigue properties of steels through the development of a unique gradient structure with the outermost compound layer (CL) and subsurface diffusion zone. The CL consisting of a heterogeneous mixture of ε-Fe2-3N and γ′-Fe4N phases presents a relatively high hardness, which makes a positive contribution to wear resistance under light loads [7][8][9]. However, this layer suffers from high internal stress, which makes it friable and brittle, and will be crushed under conditions of impact and/or heavy loads [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional gas nitriding (TGN), a typical thermochemical surface treatment, has been particularly effective in improving the hardness, wear resistance and fatigue properties of steels through the development of a unique gradient structure with the outermost compound layer (CL) and subsurface diffusion zone. The CL consisting of a heterogeneous mixture of ε-Fe2-3N and γ′-Fe4N phases presents a relatively high hardness, which makes a positive contribution to wear resistance under light loads [7][8][9]. However, this layer suffers from high internal stress, which makes it friable and brittle, and will be crushed under conditions of impact and/or heavy loads [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in creep rate of carburized material can be attributed to the presence of carbides which precipitated during pre-conditioning, significantly modifying the local material properties, including increasing the material strength and the materials resistance to creep deformation. Additionally, it is worth mentioning that near-surface carburization due to pre-conditioning would induce compressive residual stresses, beneficial for the creep resistance of the material, as a consequence of carbon ingress and subsequent carbide precipitation [36].…”
Section: Creep Performancementioning
confidence: 99%
“…It is also ideal for parts where distortion is a concern due to tight tolerances, since distortion is not typical due to the relatively low temperatures involved in the process [15]. Jegou et al [16] investigated the influence of nitriding potential, nitriding time and temperature on precipitation at grain boundaries and mechanical properties such as microhardness and residual stresses. They indicated that the development of residual stresses followed the principle of phase transformation kinetics during nitriding, and the kinetics was controlled by both the temperature and nitriding potential.…”
Section: Introductionmentioning
confidence: 99%